Pregnancy and Perinatal Outcomes of Patients With Prior Cesarean Section After a Single Embryo Transfer in IVF/ICSI: A Retrospective Cohort Study - Wang, Lin; Wang, Jing; Lu, Nan; Liu, Jiayin; Diao, Feiyang (Frontiers in Endocrinology, 2022)
Objective: The aim of the study was to investigate the influence of the previous cesarean section on the pregnancy and maternal and neonatal outcomes compared with vaginal delivery following single embryo transfer(SET)undergoing in vitro fertilization(IVF). In addition, the association between fertility outcomes and different CSD sizes was studied. Method: This was a retrospective cohort study conducted in the reproductive center of the first affiliated hospital of Nanjing medical university. A total of 4879 patients with previous delivery history undergoing single embryo transfer were included between January 2015 and April 2019. Patients were divided into the vaginal delivery (VD) group and cesarean delivery (CD) group according to different modes of the previous delivery. The primary outcome measure is live birth. The pregnancy outcomes of cesarean scar defect(CSD)were analyzed as a subgroup and the relationship between pregnancy outcomes and the different sizes of CSD were explored by logistic regression analysis. Results: There were no significant differences in live birth rate, clinical pregnancy rate, and miscarriage rate between CD group and VD group. The incidence of pregnancy complications such as placenta previa, postpartum hemorrhage, gestational diabetes mellitus, pregnancy hypertension were similar in the two groups.The live birth rate were significantly lower in the CSD group(23.77%vs 37.01%,aOR:0.609,95%CI:0.476-0.778)comparing with patients without CSD.There were also significant differences in clinical pregnancy rate (37.52%vs47.64%,aOR:0.779,95%CI:0.623-0.973)and miscarriage rate(34.55%vs20.59%,aOR:1.407,95%CI:1.03-1.923).Large CSD significantly decreased the live birth rate(13.33%vs26.29%,aOR:0.422,95%CI:0.197-0.902)and clinical pregnancy rate(25.33%vs40.09%,aOR:0.503,95%CI:0.272-0.93)compared with small CSD. Conclusion: For women with the previous CD, the pregnancy outcomes were similar to those with previous VD without increased obstetric perinatal complications following SET. The presence of CSD is associated with a marked reduction in live birth rate especially in patients with large CSD.